Aquatic habitats in sustainable urban water management science, policy and practice - Wagner, Iwona 1971-; Marsalek, J. (Jiri) 1940-; Breil, Pascal (Urban water series, 2008)
Aquatic habitats supply a wide range of vital ecosystem benefits to cities and their inhabitants. The unsustainable use of aquatic habitats, including inadequate urban water management, however, tends to alter and reduce their biodiversity and thereby diminish their ability to provide clean water, protect humans from waterborne diseases and pollutants, keep urban areas safe from flooding, and support recreational ecosystem services and even aesthetic enjoyment. This publication aims at improving understanding of aquatic habitats, related ecosystem goods and services, and conservation and sustainable use, with a special focus on their integration into urban water management.